Non-suicidal self-injury in adolescence, clinical study in psychopathology - MOHAND, Samir (Journal of Human Sciences, 2025)
Non-suicidal self-injury (NSSI) is a form of self-directed aggression commonly seen during adolescence. It is impulsive and repetitive, with individuals using it to express psychological distress through physical pain. This behavior involves deliberate actions, such as hitting, cutting, burning, or scratching, without suicidal intent, and is socially unacceptable.This paper offers a clinical psychological perspective on self-injury, viewing it as a transition from words to actions. It occurs during adolescence due to the fragility caused by psychological and physical changes, making individuals prone to using their bodies as a form of expression. NSSI reflects alexithymia, where emotional expression is poor and is instead conveyed through physical actions. It is a maladaptive coping mechanism for early traumatic experiences and an ineffective strategy for emotional regulation. Additionally, it signals difficulties in forming balanced relationships, with the body and behavior serving as a means of communication and a cry for help.